DAMPAK TEKNOLOGI AI TERHADAP TENAGA KERJA DALAM BIDANG AKUNTANSI MANAJEMEN - Sely, Sely (LPPM Politeknik Saint Paul Sorong, 2019)
This journal discusses the impact of artificial intelligence (AI) technology on management accounting. With the development of AI technology, management accounting practices are undergoing a significant transformation. The implementation of AI technology has improved operational efficiency, enriched data analysis, and supported smarter decision making. However, the adoption of AI technology also faces challenges related to understanding and necessary skills as well as data privacy and security issues. Through this journal, it was found that appropriate implementation strategies, including employee recognition, system integration, and ethical policies, are needed to maximize the benefits of AI technology in management accounting. This journal article provides valuable insights for practitioners and decision makers interested in harnessing the potential of AI technology in the context of management accounting.